Process of Mentoring in Disruptive Innovation of Organizations (GEON Journal (Management, Organizations and Business), 2017)
Modern organizations must constantly adapt to the changes they face due because globalization, where innovation, effectiveness and efficiency are the main topics to consider, so the use of adequate skills and elements from its conceptualization toward their implementation, offer the know-how to affront this challenges, and in result may increase the organizational environment toward this objectives. The new organizational practices management tools such as mentoring and innovation needs to be important part of the daily bases activities in any modern organization.     Innovation is no longer an option; it must be a normal practice in any organization management. This innovation capability must be sustainable and profitable in pursuit of new business and commercial challenges, the wall change is to stop thinking that innovation is not far from easy to organizations; but in order to change that old way of thinking we need a proper accompaniment, for achieving, looking to go further and move at a pace that allows not only for going fast, but faster in a 10x speed. It is then through the use of mentoring tool for the innovation process, that this may be possible to implement in an extraordinary way.
Keywords: Mentoring; Innovation; Management; Skills